Hodnocení finanční situace podniku a návrhy na její zlepšení - Krajčová, Aneta (Vysoké učení technické v Brně. Fakulta podnikatelská, 2024)
Tato bakalářská práce je zaměřena na zhodnocení finanční situace podniku TON a. s. za období 2019–2022. První část obsahuje teoretická východiska, objasnění základních pojmů a vybraných ukazatelů finanční analýzy. V praktické části jsou použity metody a ukazatele na vybranou firmu. Závěrečná část práce se zabývá návrhy na zlepšení finanční situace společnosti.

This bachelor's thesis is focused on the evaluation of the financial situation of the company TON a. s. for the period 2019-2022. The first part contains theoretical starting points, clarification of basic terms and selected indicators of financial analysis. In the practical part, methods and indicators for the selected company are used. The final part of the thesis deals with proposals for improving the financial situation of the company.
Evaluation of the Financial Situation of a Company and Proposals to its Improvement
Keywords: finanční analýza; rozvaha; výkaz zisků a ztrát; ukazatele finanční analýzy; financial analysis; balance sheet; profit and loss statement; indicators of financial analysis